Buddhist ordination as a culturally embedded model for improving diet, body composition, and sleep quality in overweight and obese adults - Phrarajvarjirayanamethi Chatchai Moosan; Phim On Suklaew; Charoonsri Chusak; Thanaporn Kaewpradup; Kritmongkhon Kamonsuwan; Sirichai Adisakwattana (Scientific Reports)
Abstract Buddhist ordination involves significant lifestyle changes including meal timing, diet, and sleep patterns, yet short-term physiological effects remain poorly understood. This study examined effects of two-week ordination on dietary intake, body composition, and sleep quality in newly ordained Thai Dhammayut monks. Fifty-two participants (mean age 30.03 ± 1.13 years; BMI 26.70 ± 0.46 kg/m²) underwent assessments at baseline, one week, and two weeks post-ordination. While total energy intake remained stable, macronutrient composition shifted significantly: protein decreased > 20%, sugar nearly doubled, and fiber increased substantially. Body composition improved with reductions in weight, BMI, waist and hip circumference. Muscle mass modestly decreased while body fat percentage and visceral fat remained stable. Sleep quality improved significantly, particularly sleep latency and subjective restfulness, despite unchanged efficiency. Findings suggest Buddhist ordination may produce beneficial short-term physiological adaptations similar to time-restricted eating. Though improvements in abdominal adiposity and sleep quality were observed, declining muscle mass highlights nutritional adequacy concerns. Monastic routines may provide culturally appropriate frameworks for structured lifestyle interventions.